2016
DOI: 10.1111/eva.12388
|View full text |Cite
|
Sign up to set email alerts
|

Describing a developing hybrid zone between red wolves and coyotes in eastern North Carolina, USA

Abstract: When hybridizing species come into contact, understanding the processes that regulate their interactions can help predict the future outcome of the system. This is especially relevant in conservation situations where human activities can influence hybridization dynamics. We investigated a developing hybrid zone between red wolves and coyotes in North Carolina, USA to elucidate patterns of hybridization in a system heavily managed for preservation of the red wolf genome. Using noninvasive genetic sampling of sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 79 publications
0
34
0
Order By: Relevance
“…Hinton [69–70] suggested as red wolves and coyotes approached each other in body size, similar use of prey and space may reduce behavioral incompatibilities between consorting individuals and permit the successful formation of congeneric pairs responsible for creating red wolf/coyote hybrids. Because hybridization is a primary threat to the conservation and persistence of eastern wolves [14,18,7172] and red wolves [3,16,38,2122,73], we suggest further studies are needed to better understand behaviors and conditions that allow individuals of Canis populations to successfully form congeneric breeding pairs responsible for hybridization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hinton [69–70] suggested as red wolves and coyotes approached each other in body size, similar use of prey and space may reduce behavioral incompatibilities between consorting individuals and permit the successful formation of congeneric pairs responsible for creating red wolf/coyote hybrids. Because hybridization is a primary threat to the conservation and persistence of eastern wolves [14,18,7172] and red wolves [3,16,38,2122,73], we suggest further studies are needed to better understand behaviors and conditions that allow individuals of Canis populations to successfully form congeneric breeding pairs responsible for hybridization.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Hinton et al [3] reported increased occurrence of coyote encroachment and replacement of resident red wolves after resident wolf breeders were killed by humans. Although red wolves exhibit assortative mating patterns [16,38], coyotes were capable of pair-bonding with surviving red wolves when no transient wolves were available to encroach into territories that were disrupted by anthropogenic mortality [3]. Consequently, pair-bonding with coyotes by surviving red wolf residents formed congeneric breeding pairs that hybridized [3,22,33].…”
Section: Introductionmentioning
confidence: 99%
“…For some species, hybridization and introgression are major threats to population and species persistence creating a need for long‐term genetic monitoring (Allendorf, Leary, Spruell, & Wenburg, ). Genetic monitoring approaches using MIS have been applied to detect hybridization in multiple carnivore species including grey wolves (Caniglia et al., ; Godinho et al., ; Kopaliani, Shakarashvili, Gurielidze, Qurkhuli, & Tarkhnishvili, ; Monzón, Kays, & Dykhuizen, ), Eastern wolves ( Canis lycaon , Benson, Patterson, & Wheeldon, ), red wolves ( Canis rufus ; Adams et al., ; Bohling et al., ) and wildcats ( Felix silvestris silvestris ; Anile, Ragni, Randi, Mattucci, & Rovero, ; Steyer et al., ). The majority of these studies have used mitochondrial DNA and microsatellite markers, but a few have used SNPs to detect hybridization or monitor grey wolves (Kraus et al., ; Monzón et al., ) and hybridization between wildcats and domestic cats (Nussberger et al., ; Oliveira et al., ).…”
Section: Questions and Metrics That Can Be Investigated With Mismentioning
confidence: 99%
“…Factors influencing assortative mating in Canis taxa are likely multifaceted with a diversity of behavioral and ecological correlates that may influence hybridization (Benson & Patterson, ; Bohling et al., ; Hinton et al., ; Hinton, Ashley et al., ; Rutledge, Garroway et al., ; Rutledge, White et al., ). Essentially, hybridization results when individual red wolves and coyotes consort to form congeneric breeding pairs that defend territories and produce hybrid litters (Hinton et al., ; Hinton, Brzeski et al., ; Hinton, Ashley et al., ).…”
Section: Introductionmentioning
confidence: 99%